Optoelectronic and electromyographic study of the erector spinae muscle in female patient aged 8 with scoliosis - Karolak, Przemysław; Karolak, Joanna; Wilczyński, Igor; Wilczyński, Jacek (Journal of Education, Health and Sport, 2017)
Abstract The aim of the research was an optoelectronic and electromyographic analysis of the erector spinae muscle in patient aged 8. For the analysis there were used Diers Formetric III 4D system and Noraxon TeleMyo DTS receiver. The first one is used for optoelectronical defining of the curvature of the spine. In turn, Noraxon is used for recording and analyzing the myoelectric signals coming from the muscle. Two measurements were carried out at the interval of six months. Depending on the segment of the spine, and also whether the mean amplitude or frequency was examined, the measurements showed a higher frequency for both segments in the concave side while the larger amplitude in the concave side only in the thoracic spine. In the lumbar spine the amplitude was higher in the convex side.